다양한 식사섭취 조사방법을 활용한 비만 초등학생의 식생활 실태 분석 - 윤혜빈(Hye Bin Yoon); 송진선(Jin Seon Song); 한영신(Youngshin Han); 이경아(Kyung A Lee) (Journal of nutrition and health, 2023)
Purpose: Childhood obesity has become a social problem due to the social distancing necessitated by the coronavirus disease 2019 pandemic. This study aimed to identify the dietary problems of obese children through various dietary assessment methods and to confirm the usefulness of each method. Methods: The subjects were 88 students in the 4th to 6th grade of elementary school who participated in the nutrition camp organised by the Busan Metropolitan Office of Education, 2020. To evaluate dietary problems and assess diet quality, 24-hour meal records, monthly food intake frequency, and Dietary Screening Test (DST) data were analyzed. Results: Of the subjects, 15.7%, 30.3%, and 53.9% were normal weight, overweight, and obese, respectively. The average age was 11.77 ± 0.77 years and the average body mass index was 23.96 ± 3.01 kg/m2. It was observed from the 24-hour meal record method that the overweight and obese subject groups consumed fewer green vegetables (p < 0.001) and white vegetables (p < 0.01) than the normal weight group. In the monthly food intake frequency method, the consumption of ramen (p < 0.01), snacks (p < 0.05), and sausages (p < 0.05) were high in the obese group, and that of anchovies, broccoli, and sweet pumpkin was high in the normal group (p < 0.05). The comparative data from the DST revealed that the overweight and obese groups had less vegetable intake than the normal weight group (p < 0.01) and had higher intakes of dairy products, fast food, and sweet snacks (p < 0.05). Conclusion: The usefulness of each method in the dietary evaluation of obese children was confirmed. To address the problem of obesity, it is necessary to evaluate the dietary problem and approach it with a customized solution tailor-made for the individual subject. COVID-19로 인한 사회적 거리 두기 실천으로 소아 비만 증가하였고 비만 학생 대상 영양교육 및 상담의 필요성이 증가하고 있다. 이에 비만 초등학생의 식생활 문제점을 분석하여 비만 개선을 위한 영양교육 및 영양상담 시 활용할 수 있는 기초자료를 제공하고자 하였다. 본 연구는 2020년 부산시교육청 주관 영양캠프에 참여한 초등학생 4-6학년 88명을 대상으로 사진 활용 24시간 식사기록, 한 달 간의 식품섭취빈도 조사, DST 식습관 조사를 활용하여 식생활 실태를 분석하였다. 조사 대상자는 남학생 46.6%, 여학생 53.4%로 정상체중군 15.7%, 과체 중군 30.3%, 비만군 53.9%이다. 조사대상자의 평균 연령은 11.77 ± 0.77세, 평균 신장은 147.44 ± 8.08 cm, 평균 체중은 53.47 ± 1.56 kg, 평균 체질량지수는 23.96 ± 3.01 kg/m2 이었다. 사진활용 24시간 식사기록 조사 결과, 과체중군과 비만군이 정상체중군보다 녹색 채소류 (p < 0.001)와 흰색 채소류 (p < 0.01)의 섭취가 적었으며, 한 달 간의 식품섭취빈도 조사를 식품군으로 묶어 조사한 결과에서는 어패류 (p < 0.01)와 녹색 채소류 (p < 0.05)의 섭취빈도가 낮아 유의한 차이를 보였으며, 81가지 식품을 나누어 분석한 결과에서는 비만군이 정상체중군보다 라면 (p < 0.01)과 스넥과자류 (p < 0.05)의 섭취빈도가 높고 비만군이 정상체중군과 과체중군보다 탄산음료 (p < 0.01), 햄, 소시지 (p < 0.05)의 섭취빈도가 높은 반면, 과체중군과 비만군이 정상 체중군보다 멸치 (p < 0.05)와 브로콜리 (p < 0.05), 단호박 (p < 0.05)의 섭취가 낮아 유의한 차이를 보였다. DST 식습관 조사를 비교한 결과, 과체중군과 비만군이 정상체중군보다 채소류 (p < 0.01) 섭취가 낮은 반면, 유제품 (p < 0.05)과 단 간식 (p < 0.05) 섭취가 높게 나타나 유의한 차이를 보였다. 이상의 결과는 비만 아동의 문제를 해결하기 위해 다양한 방법을 활용하여 식생활 문제를 평가하고 개인 문제에 맞는 해결 방법으로 접근해야 함을 시사한다.